2022
DOI: 10.1093/mnras/stac2639
|View full text |Cite
|
Sign up to set email alerts
|

Automated galaxy–galaxy strong lens modelling: No lens left behind

Abstract: The distribution of dark and luminous matter can be mapped around galaxies that gravitationally lens background objects into arcs or Einstein rings. New surveys will soon observe hundreds of thousands of galaxy lenses, and current, labour-intensive analysis methods will not scale up to this challenge. We develop an automatic, Bayesian method which we use to fit a sample of 59 lenses imaged by the Hubble Space Telescope. We set out to leave no lens behind and focus on ways in which automated fits fail in a smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…The latter is the best match to our networks, and is comparable in performance, as mentioned in S21a. There is also currently a lot of work going into automated modeling without machine learning (e.g., Nightingale et al 2018Nightingale et al , 2021Rojas et al 2022;Savary et al 2022;Ertl et al 2023;Etherington et al 2022;Gu et al 2022;Schmidt et al 2023), which typically performs better than neural networks but requires significantly longer run times of hours to days. We refer to Schuldt et al (2022) for a direct comparison between the network presented here and traditionally obtained models for real HSC lenses.…”
Section: Network Results and Performancementioning
confidence: 99%
“…The latter is the best match to our networks, and is comparable in performance, as mentioned in S21a. There is also currently a lot of work going into automated modeling without machine learning (e.g., Nightingale et al 2018Nightingale et al , 2021Rojas et al 2022;Savary et al 2022;Ertl et al 2023;Etherington et al 2022;Gu et al 2022;Schmidt et al 2023), which typically performs better than neural networks but requires significantly longer run times of hours to days. We refer to Schuldt et al (2022) for a direct comparison between the network presented here and traditionally obtained models for real HSC lenses.…”
Section: Network Results and Performancementioning
confidence: 99%
“…Forming robust quantitative goodness-offit metrics is currently an open problem in automated lens modeling. Etherington et al (2022) explored this problem using P A L with much higher resolution images and found that none did a particularly satisfactory job. We take the Bayesian evidence to be the reference figure of merit and follow this with a blind visual inspection of the image, fit, and spectrum of each modeled candidate.…”
Section: Model Quality Assessment and Gradingmentioning
confidence: 99%
“…For most of galaxy-scale lenses, their Einstein radii are typically smaller than their half-light radii, making it difficult to clearly identify the relatively faint lensed images. In order to subtract the foreground light distributions, parametric light profiles, e.g., Sérsic or double Sérsic profiles (Bolton et al 2008;Shajib et al 2019;Birrer et al 2020;Etherington et al 2022), are usually adopted as fitting models. However, these profiles with a limited number of parameters may result in undesired residuals, especially for the light distributions with complex angular structures.…”
Section: Subtraction Of Lens Galaxy Lightmentioning
confidence: 99%
“…Usually, the Einstein radius is deemed to be such a quantity (Schneider et al 2006;Treu 2010). Its measurement error is typically of the order of a few per-cent (Bolton et al 2008;Shu et al 2015Shu et al , 2016Shajib et al 2021;Etherington et al 2022). However, there are also works showing surprising results.…”
Section: Introductionmentioning
confidence: 99%